Sources of the Competitive Advantage of Family Enterprises: An International Approach Focusing on China, Nigeria and Poland - Joanna Bednarz; Tomasz Bieliński; Anna Nikodemska-Wołowik; Ade Otukoya (Entrepreneurial Business and Economics Review)
Objective: The objective of this paper is to identify some crucial factors influencing family businesses in China, Nigeria and Poland through a prism of the competitive advantage theory as well as company values. Research Design & Methods: The empirical research results were employed: findings from a survey on competitive advantage, from a study of Family Enterprises’ (FEs) survival in Nigeria, from interviews conducted with the owners of Polish FEs, from a survey with Polish consumers, and from interviews conducted with FEs’ managers in China. International desk research was carried out as well. Findings: Major attributes of FEs which can support their competitive advantage created on the market were identified. The significance of family enterprises in contemporary economies of China, Nigeria and Poland was examined. Implications & Recommendations: The success of FEs and their important nature mean that more research is needed to understand their development for the future. A holistic and cross-cultural approach is required. As the consumers’ attitudes towards FEs in the three countries differ ignificantly, a unified survey which can be adjusted for the cultural requirements of each country is recommended. Contribution & Value Added: While comparing FEs in the three countries, some crucial factors which influence their functioning were discovered. Despite of identified obstacles in performance of FEs, there are some sources of CA highlighted and divided into similarities, differences and autonomous features by the authors.